Economics of a feeding budget: A case of diversity of host plants for Lymantria dispar L. (Lepidoptera) feeding on leaves and needles - Soukhovolsky, Vladislav; Tarasova, Olga; Pavlushin, Sergey V.; Osokina, Ekaterina; Pavlushin, Sergey V.; Osokina, Ekaterina; Akhanaev, Yuriy; Kovalev, Anton; Martemyanov, Vyacheslav V. (Diversity)
Relationships were analyzed among the energy-related characteristics of feed consumption by caterpillars of the spongy moth (also known as gypsy moth) Lymantria dispar L., survival of individuals, and fecundity of females depending on the species of a host plant. An optimization model of feed consumption was used for the calculations. In this model, efficiency of consumption depends on two parameters: efficiency of metabolic degradation of feed and efficiency of caterpillar biomass synthesis. Experiments were conducted regarding the feeding of caterpillars on the leaves of silver birch Betula pendula Roth. and needles of Siberian larch Larix sibirica Ldb. and Scotch pine Pinus sylvestris L. On the basis of the results of experiments, "costs" of the feed for females and males were calculated, the consumption efficiency of different types of feed was found, and the relationship between efficiency of feed consumption and female fecundity was determined. The proposed approach can be employed to assess feeding efficiency of insects in various habitats.